Impact of nutrition education intervention on nutritional status of undernourished children (6-24 months) in East Mamprusi district of Ghana. Issue 2 (26th October 2018) - Awuuh, Vincent Adocta; Appiah, Collins Afriyie; Mensah, Faustina O.
Abstract : Purpose: This study aims to determine the impact of nutrition education intervention on nutritional status of undernourished children aged 6-24 months in the East Mamprusi district of Ghana. Design/methodology/approach: This was a pre-post interventional study. In all, 153 undernourished children of age 6-24 months and their mothers were recruited from five communities. Underweight, stunting, wasting, mid upper arm circumference (MUAC) and haemoglobin (Hb) levels were determined at baseline and after intervention. Nutrition education was given to the mothers for three months based on the nutrition problems identified at baseline assessment. Findings: There were improvements in underweight, wasting, MUAC and Hb levels among the children after the nutrition education intervention. The level of improvement at post-intervention differed significantly for underweight (−2.4 ± 0.4, −2.2 ± 0.4; p = 0. 001), wasting (−2.2 ± 0.6, −1.9 ± 0.6; p = 0. 001), MUAC (12.3 ± 0.5, 12.9 ± 0.6; p = 0. 001) and Hb level (10.0 ± 1.4, 10.5 ± 1.4; p = 0. 001) of the children compared to pre-intervention (−1.4 ± 1.8, −1.3 ± 1.7; p = 0.314). Practical implications: There was significant improvement in the nutritional status of the undernourished children after the nutrition education intervention. Community nutritionists and stakeholders involved in nutrition and health issues concerning infants and young children should consider nutrition education, as it could be an inexpensive and effective strategy in combating childhood undernutrition in resource-poor settings. Originality/value: Findings of this study provide evidence, suggesting nutrition education as a potential strategy to curb the high rates of child undernutrition in resource-poor communities in Ghana. This study provides insight for larger studies on the effectiveness of nutrition education in curbing child malnutrition in deprived communities in Ghana.